Problems in Studying English Language Among Future Engineers - E. A. Kogan; O. B. Krymskaya (Высшее образование в России)
The article presents the results of a research conducted among students of MAI (NRU) and MADI in order to find out the difficulties they face in the process of learning a foreign language in the framework of the compulsory course. The research was conducted by questionnaire. The students of the 1-3 courses of MAI and MADI, studying engineering and English language were interviewed.It was revealed that future engineers are aware of the demand for English in their professional activities, and the main objectives of studying of the language at the University are verbal professional and personal communication (communication with foreign colleagues, as well as with friends and acquaintances). At the same time, educational motivation (mastering of educational literature, obtaining a credit) turned out to be less significant.Students consider the discussion to be the most effective method of educational activity. More than a quarter of the students admit that they lack knowledge gained at school to master the English language course successfully, as a result they lack a vocabulary and have difficulties with grammar, pronunciation and translation. Lack of time and motivation prevents them from overcoming these problems. To improve the motivation of studying English, the researchers propose to use a variety of methods, in particular, role-playing, work in pairs, discharge, etc.Mastering English language is also hindered by organizational problems – the lack of speaking practice in the classroom, a small number of classes per week, large group size, high speed of passing through language material and a significant amount of homework. The research revealed students’ wishes regarding the optimization of the English language course at the University. Future engineers would like more attention to be paid to speaking practice, communication with native speakers, watching videos as part of the English compulsory course.